Guidance document on the validation of (Quantitative) structure-activity relationship [(Q)SAR] models (Paris, 2007)
The solid scientific foundation for (Q)SAR technology is the underlying premise in chemistry that similar chemical structures are expected to exhibit similar chemical behaviour. This simple premise becomes especially important whenever there are not enough empirical data for hazard identification and risk assessment purposes. With tens of thousands of chemical structures to assess and many different empirical tests needed to understand chemical behaviour, the concept of grouping similar chemicals together and extending existing data through models for similar chemical structures which have not been tested seems to be a prudent approach .
Keywords: Hóa học,Chemicals; Các biện pháp an toàn,Safety measures